Association between APOE ε4 Genotype and Memory Impairment in Elderly with Normal Global Cognitive Assessment - Turana, Yuda (Diagnostics (Basel), 2015)
Aim: Early prediction using cognitive evaluation tools that are less influenced by education level is beneficial for dementia screening. This study investigated the relationship between Word List Memory Immediate Recall (WLM IR) and the Saving Score (SS) with having the APOE ε4 risk allele in the elderly with normal global cognitive assessment. Methods: A cross-sectional study on 105 subjects ≥60 years with normal MMSE scores who met inclusion criteria. Memory impairment (MI) if: WLM IR score on the third trial <8 or an SS score <80%. Results: The majority of the subjects were female (68.6%), 65 ± 7.1 years, had undertaken formal education for <6 years (56.2%), had MI (81%), and the APOE ε4 genotype was detected in 24.8% of subjects. There was a significant relationship between APOE ε4 and lower WLMIR (p = 0.02, OR 7.92, CI 95% (1.00–62.38)). Conclusions: WLM IR score is lower in elderly people with the APOE ε4 despite their normal global cognitive assessment results, and these scores were not influenced by education level. Further research needs to confirm that the WLM IR can be used to screen for early dementia.